Functional analysis of DAZL-mediated translation activation during mammalian gametogenesis - Sousa Martins, Joao Pedro; Martins, Joao Pedro (The University of Edinburgh, 2012)
Gametogenesis is a highly complex process that requires stringent control of gene expression, in which translational regulation plays an essential role. Deleted in Azoospermia-like (DAZL) belongs to the DAZ family of RNA-binding proteins, which are restricted to germ cells, and regulate mRNA translation. Importantly, loss of function of these proteins results in infertility in both males and females in a wide variety of organisms. A model for the mechanism by which DAZL stimulates translation has been proposed based on work in Xenopus laevis (X. laevis) oocytes. In this model, DAZL functions by recruiting the translation initiation factor poly(A)-binding protein (PABP) to the 3’ untranslated region (UTR) of messenger RNAs. Simultaneous binding of PABP to Dazl and factors at the 5’ end confers a “closed-loop” mRNA conformation, which promotes translation initiation. To examine whether DAZL plays a similar role in mammals, co-expression of Dazl and PABP family members was investigated in fetal and adult mouse gonads. In contrast to X. laevis, mammals encode four cytoplasmic PABPs which share a similar domain organisation: PABP1, tPABP, ePABP and PABP4, of which PABP1 and PABP4 appear to be expressed in a wide range of tissues. Immunohistochemistry revealed that Dazl, Pabp1 and Pabp4 are all expressed in primordial germ cells (PGCs) but these show different expression patterns following germ cell sex differentiation. In adult testes Dazl is expressed in spermatogonia and spermatocytes, coinciding with the peak of Pabp4 expression. In contrast, the peak of Pabp1 expression occurs later than that of Dazl, with these proteins only being co-expressed in late pachytene and secondary spermatocyte phases. In adult ovaries, Pabp1, Pabp4 and Dazl are all expressed in the oocytes of primordial and primary follicles. Since both PABP family members are co-expressed with Dazl, the ability of DAZL to interact with PABP1 and PABP4 was investigated in vitro and in vivo. Surprisingly, these studies showed that DAZL discriminates between different PABP family members, only interacting with PABP1, providing the first report of a PABP-specific protein partner. Several putative DAZL mutations have been identified in patients with impaired fertility. Two of these mutations, I37A and R115G, are located in the RNA recognition motif (RRM), a domain which is found in many RNA-binding proteins and mediates both RNA and protein interactions. Thus, the role of these mutations in the ability of DAZL to stimulate translation was investigated. To this end, a translational target of human DAZL (hDAZL) was sought. The 3’UTR of growth differentiation factor 9 (hGDF9) mRNA was found to confer regulation by hDAZL and thus the ability of mutant DAZLs to stimulate reporter mRNAs containing this 3’UTR was examined. This revealed that both mutations compromised the ability of hDAZL to stimulate hGDF9 translation, suggesting a causative effect. These results were further confirmed in assays in which hDAZL is artificially tethered to mRNAs. The ability of mutant hDAZLs to stimulate translation in this assay was compromised suggesting that loss of function is, at least in part, due to impaired protein-protein interactions rather than altered RNA-binding. This work provides insights into the molecular mechanism by which DAZL stimulates the translation of specific mRNAs during mammalian gametogenesis and provides evidence that this function may play an important physiological role in human reproduction.
Keywords: DAZL; Deleted in Azoospermia-like; gametogenesis; PABP